Stress analysis of nano porous material using computed tomography images. Issue 3 (7th March 2019) - Meyghani, B.; Awang, M.; Emamian, S.; Plank, B.; Heinzl, C.; Siow, K.S.
Abstract: Sintered silver materials possess an advantage that allows excellent bonding between chips and their substrate. Stress manifests as the materials resistance against external and internal forces, however during stress analysis the complex physical behavior caused by the forces and the nature of the material is often disregarded by researchers. This paper analyses the stress behavior of nano porous sintered silver in X and Y directions using finite element modelling. This study also focuses on observing the growth of the crack in samples in different directions. It is found that the occurrence of the cracks in the specimens starts at the peak stress point and the failure is observed at the largest void. It is also detected that the stress across the whole area of the model is regularly distributed in those samples which have relatively smaller voids. Thus, these samples have a better material integrity. In addition, this fact indicates that the material in these sample could hold higher levels of stress. Finally, the level of the stress and the possibility of failure in those samples that have smaller voids is found to be less than others.